On laguerre matrix polynomials - Jódar, Lucas; Sastre, Jorge (Utilitas Mathematica, 1998)
In this paper generalized hypergeometric matrix functions are introduced. Properties of Laguerre matrix polynomials and their connections with hypergeometric and Bessel matrix functions are established. Formulas for the generating function of products of Laguerre matrix polynomials extending well-known formulas for the scalar Laguerre polynomials are given.